The first hospital and the construction of leprosy - Elmore, Matthew (Dialog, 2022)
This essay presents the first hospital as an icon of the divine nature. Established by St. Basil in the fourth century, the hospital reconstructed the social meaning of disease and poverty. I contrast its work with my own experience working in the emergency department of a small urban hospital, where patients with low social capital were treated with contempt. I suggest that the first hospital deserves a prominent place in our collective memory, because it exemplifies a threefold ideal relevant to modern healthcare. Ethically, it promoted radical human equality. Economically, it transcended former concepts of repayment. And historically, it stands as the precedent of an indispensable institution.